Immunogenicity of small‐cell lung cancer associates with STING pathway activation and is enhanced by ATR and TOP1 inhibition - Xuetao Li; Yujun Li; Ziwen Zhao; Nabo Miao; Guorong Liu; Liaoyuan Deng; Shuquan Wei; Jun Hou (Cancer Medicine, 2023)
Abstract Introduction The activation of STING (stimulator of interferon genes) pathway enhances antitumor immunity in small‐cell lung cancer (SCLC), while the DNA damage induced by non‐cGAMP‐based agonists is a potent inducer of STING activity. Here, we investigate the intrinsic expression of STING in cancer cells and evaluate the value of the combination of ATR and TOP1 inhibitors in enhancing antitumor immunity. Methods STING expression was assessed at mRNA and protein levels in SCLC and normal lung tissues. Transcriptomic subsets of SCLC were identified based on STING‐related genes. Distinct mutation and immunogenomic profiles of these subsets were determined. The direct antitumor efficacy and the potential of enhancing antitumor immunity of the strategy using the ATR‐TOP1‐inhibitor combination were tested in SCLC cell lines. Results The intrinsic expression of STING was significantly reduced in SCLC compared to normal lung tissues (p < 0.0001). Three STING‐related SCLC subtypes were identified in which the STING‐high subtype was associated with (1) high immune infiltration, (2) high expression of genes related to MHC and immune checkpoints, and (3) high EMT and ferroptosis score. On the contrary, the STING‐low subtype was enriched with pathways related to DNA damage response (DDR) and cell cycle progression. The association between the DDR pathway activity and the STING‐IFN innate immune response was verified by in vitro experiments in which the inhibition of ATR and TOP1 triggered the expression of genes encoding type I IFN signaling and pro‐inflammatory cytokines/chemokines in a STING‐low SCLC cell line. Conclusion Our study verifies that activation of the STING‐IFN response by ATR and TOP1 inhibitors might be a therapeutic strategy to improve the response to immune checkpoint therapy in STING‐low SCLC. Furthermore, the combinations of ATR and TOP1 inhibitors can augment tumor inflammation in STING‐low SCLC.